The Role and Importance of Promoting Publishing in English in the Republic of Serbia - Popović Šević, Nevenka J.; Jelić, Zorica Lola Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The purpose of this paper is to explore the importance of publishing in English in the Republic of Serbia. From a scientific point of view, this work analyses the significance of translated journals, textbooks, and monographs. Due to publishing their works in English, Serbian researchers, scientists, and writers have become internationally seen and recognizable. The discussed visibility and distribution contribute to the global exchange of culture and knowledge. This paper presents reviews and statistics regarding the importance of translations of written works, which are intended for a broader audience. Undeniably, apart from its cultural and academic importance, publishing in English is also a strategically planned politics of presenting and promoting Serbian academic writing, research, and literature to the world. Through this endeavour, our country disseminates its international presence while building a competitive publishing industry.
Keywords: publications in English; scientific papers; translation; readership; the Republic of Serbia